2018
DOI: 10.1002/jbm.a.36550
|View full text |Cite
|
Sign up to set email alerts
|

An overview of nanoscale radionuclides and radiolabeled nanomaterials commonly used for nuclear molecular imaging and therapeutic functions

Abstract: Recent advances in the field of nanotechnology applications in nuclear medicine offer the promise of better diagnostic and therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 237 publications
(554 reference statements)
0
46
0
Order By: Relevance
“…According to the "magic bullet" ("Zauberkugel") approach proposed by Paul Ehrlich (1900), the cytotoxic payload is delivered selectively to the malignant cells [22]. The vectors can be represented by small molecules, peptides, antibodies, or antibody derivatives, as well as by nanocarriers (as a full review of these would be exceeding the limits of this article, please refer, for instance, to [23][24][25][26][27][28]). [ 223 Ra]RaCl 2 , however, represents an exception due to its intrinsic bone-targeting properties, mimicking the chemical behavior and metabolic pathway of calcium, as both elements belong to the alkali earth metals.…”
Section: Introductionmentioning
confidence: 99%
“…According to the "magic bullet" ("Zauberkugel") approach proposed by Paul Ehrlich (1900), the cytotoxic payload is delivered selectively to the malignant cells [22]. The vectors can be represented by small molecules, peptides, antibodies, or antibody derivatives, as well as by nanocarriers (as a full review of these would be exceeding the limits of this article, please refer, for instance, to [23][24][25][26][27][28]). [ 223 Ra]RaCl 2 , however, represents an exception due to its intrinsic bone-targeting properties, mimicking the chemical behavior and metabolic pathway of calcium, as both elements belong to the alkali earth metals.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have been done regarding the application of AuNPs for theranostics, their therapeutic function is mostly based on the photothermal properties of the AuNPs themselves or on the delivery of a payload acting as a cytotoxic drug [40][41][42][43][44][45][46]. There are some examples of AuNPs that have been evaluated in the delivery of medically relevant radionuclides, aiming to obtain "radiotheranostic" agents suitable to provide clear and sensitive tumor detection and selective therapeutic effects [47,48]. This included nanoconstructs decorated with bombesin (BBN) analogues, a bioactive peptide with high affinity towards the Gastrin Releasing Peptide receptor (GRPr) overexpressed in a variety of human cancers, and demonstrated that the AuNPs displayed specificity towards GRPr overexpressing tumors [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Radiolabeling methods yield nanomaterials used for the therapy and diagnosis of cancers [1][2][3][4][5][6][7][8][9][10] including for therapy of liver cancer (microspheres, arterial infusion), [11][12][13][14][15] and for sentinel lymph node delineation. [16][17][18][19][20][21] Here we examine a wide range of metals including many with radioactive isotopes used for diagnostic imaging or radionuclide therapy, for their ability to bind to the superparamagnetic iron oxide (SPION) nanoparticle (NP) known as Feraheme (FH), a drug approved for treating iron anemia and used off label as an MR contrast agent.…”
Section: Introductionmentioning
confidence: 99%